Improving the decision to switch from first- to second-line therapy in multiple sclerosis: A dynamic scoring system. (February 2023) - Sabathé, Camille; Casey, Romain; Vukusic, Sandra; Leray, Emmanuelle; Mathey, Guillaume; De Sèze, Jérôme; Ciron, Jonathan; Wiertlewski, Sandrine; Ruet, Aurélie; Pelletier, Jean; Zéphir, Hélène; Michel, Laure; et al.
Background: In relapsing-remitting multiple sclerosis (RRMS), early identification of suboptimal responders can prevent disability progression. Objective: We aimed to develop and validate a dynamic score to guide the early decision to switch from first- to second-line therapy. Methods: Using time-dependent propensity scores (PS) from a French cohort of 12, 823 patients with RRMS, we constructed one training and two validation PS-matched cohorts to compare the switched patients to second-line treatment and the maintained patients. We used a frailty Cox model for predicting individual hazard ratios (iHRs). Results: From the validation PS-matched cohort of 348 independent patients with iHR ⩽ 0.69, we reported the 5-year relapse-free survival at 0.14 (95% confidence interval (CI) 0.09–0.22) for the waiting group and 0.40 (95% CI 0.32–0.51) for the switched group. From the validation PS-matched cohort of 518 independent patients with iHR > 0.69, these values were 0.37 (95% CI 0.30–0.46) and 0.44 (95% CI 0.37–0.52), respectively. Conclusions: By using the proposed dynamic score, we estimated that at least one-third of patients could benefit from an earlier switch to prevent relapse.